A Democratização da Prova no Processo Civil: a ilicitude como ponto cego - Vieira, Gustavo Silveira (Universidade do Vale do Rio dos Sinos, 2017)
To think of probative law autonomously, beyond a purely procedural perspective, it is of the utmost importance for this fundamental right to be properly used by all the operators of the Law, in its broadest form and in all its complexity, aiming at the maximum efficiency of the means of proof for the protection of rights. Effectiveness, legal certainty and instrumentality are requirements that guide the contemporary Civil Process, so it is necessary that such values be conjugated in a dialectical and balanced way, so that only then be possible a correct distribution of functions between all those who participate in the process. Necessarily, these functions can only be well exercised if the participants in the process understand the correct way to go through the instructional phase with the proper use of all available evidence. The delivery of a fair decision for the proper and effective protection of rights emerges as the main objective of the process, leaving aside what has long been regarded as its primary purpose: the elimination of litigation. Being the Law - and the Civil Process itself - a cultural phenomenon, the fruit of a historical evolution, obviously that brings in its context logical guidelines, ethical principles and social habits that propagate in time through the most diverse mentalities of each epoch. It is facing this background that the evidentiary law must be analyzed and, only then, the related problems that involve the illicit evidence. As intuitive one, it is necessary to combat any pretension that seeks to relativize constitutional norms, as is the case of the rule prohibiting unlawful evidence. However, it must be admitted that there are cases so complex that it is not possible to find a ready response in the legal order, and it is precisely in these exceptional cases, that the principle of proportionality, if correctly used, can serve as an effective instrument to curb excesses.
Keywords: Direito probatório; Prova ilícita; Decisão judicial; Princípio da proporcionalidade; Probative law; Unlawful evidence; Judicial decision; Principle of proportionality; ACCNPQ::Ciências Sociais Aplicadas::Direito